Car User Taxes, Quality Characteristics, and Fuel Efficiency Household Behaviour and Market Adjustment. (1st September 2014) - De Borger, Bruno; Rouwendal, Jan
We study the impact of car user taxes on vehicle quality and demand for kilometres. First, holding car prices fixed, we find that a higher fuel tax leads households to choose cars of better fuel efficiency, provided that the demand for car use is inelastic. Surprisingly, a higher kilometre tax reduces the demand for fuel efficiency. Next, we study how car prices react to the tax changes. Fuel taxes make owning very fuel-efficient cars more expensive, while reducing prices of cars of low fuel efficiency. Both fuel taxes and kilometre charges imply lower prices for large and powerful cars.